Equity and Prevention of Cardiovascular Diseases in Latin America and the Caribbean - Eugenia Ramos; Monica Andreis; Craig Beam; Ronnie Bissessar; Deborah Chen; Marielba Cordido; Javier Valenzuela; Andreas Wielgosz; Nathan Wong (Ubiquity Press, 2022)
Non-communicable diseases, particularly cardiovascular diseases, are the leading cause of decreased life expectancy and death in Latin America and the Caribbean. Although a lifestyle, which includes no tobacco use, good nutrition, and regular physical activity is touted as key to health, the environmental, racial, social and economic conditions, which underpin lifestyle are often ignored or considered only secondarily. Placing the main responsibility on a patient to change their lifestyle or to simply comply with pharmacological treatment ignores the specific conditions in which the individual lives. Furthermore, there are major disparities in access to both healthy living conditions as well as access to medical care. There is sufficient evidence to support advocating for policies that support healthy living, particularly healthy food choices. Progress is being made to improve the food environment with enactment of front of package nutritional labels. However, policies were enacted only after intense regional research and advocacy supporting their implementation. Government officials must rise above the pressures of commercial interests and support health-promoting policies or be exposed as self-interest groups themselves. Strong advocacy is required to persuade officials that all policies should take health into consideration both to improve lives and economies.